Mitigasi Permukiman Tepi Sungai di Kelurahan Mlatiharjo - H.N. Nugroho; N. Alfibrian; M.R.D. Sabana; D. Labiba; T. Mintiea; S.E. Gunawan; A.M. Ulfa; N. Perwitasari; I.N. Sinaga; N.M. Samosir (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2019)
Semarang City is passed by Sungai Banjir Kanal Barat dan Sungai Banjir Kanal Timur which is the purpose of development of these two canals as a form of flood prevention in Semarang city because Semarang city is prone to flood disaster. Floods that occur in Semarang city can be divided into three sources, namely flood shipment generally comes from the upper regions such as Semarang regency, especially Ungaran District, local floods that are the result of river water flows and times, and rob floods coming from tidal water area Coastal Semarang. Although the construction of artificial river has been done by the government of Semarang City, until now the flood is still one of the main problems that hinder the growth and development of Semarang City. The government has made efforts to normalize the Sungai Banjir Kanal Barat, but until now has not been able to do the normalize Sungai Banjir Kanal Timur. The method used in this research is quantitative method that uses secondary data to be processed and qualitative method in the form of gathering perspective of people living on the banks of BKT River, precisely in Mlatiharjo RW IV and RW V Village by way of interview and direct observation. The final result of this research is siteplan design area, the result of design analysis, management and financing management, and recommendation. The concept offered is Mlatiharjo Eco Riverfront Settlement Mitigation, a design concept that focuses on reducing flooding with disaster mitigation efforts.